Cría y ceba de ovino africano: explotación de codornices. - Ospina Galindo, Georgina Liliana; Vargas Sánchez, Julio Ernesto (Instituto Colombiano Agropecuario - ICA, 2018)
Ovinos-Ganado ovino - Ovis aries